IMPLEMENTASI APLIKASI “SIAS / SISTEM INFORMASI AKUNTANSI SEKOLAH” DALAM PENYUSUNAN LAPORAN KEUANGAN SEKOLAH MUHAMMADIYAH DI KABUPATEN BOJONEGORO - Syaiful, Syaiful; Anugrah, Indra Gita; Aufa, Muhammad; Tumirin, Tumirin; Suwarno, Suwarno (Jurnal Pengabdian Masyarakat dan Lingkungan, 2024)
Community service activities aim to provide understanding and skills for the Muhammadiyah School Treasurer in Bojonegoro Regency regarding the preparation of financial reports using the "SIAS / School Accounting Information System" application. Community Service begins by giving a pre-test to participants so that the presenter can find out to what extent the material or materials to be taught have been mastered by participants regarding asset management. The next stage is counseling about the use of the application. The final stage is the final evaluation / post-test which is used to determine participants' understanding of the material that has been provided. The methods used in service activities are lectures, training and assistance in using the SIAS application. The result of this service is to provide literacy to Muhammadiyah School Treasurers so they are able to understand and apply the use of the SIAS application so that in the future they can organize and manage finances properly and correctly. This activity provides positive value in terms of effectiveness and efficiency in managing school finances.